KOMUNIKASI ORGANISASI TATA KELOLA ANGGARAN DAERAH (Studi Kasus Festival Anggaran III-2017 Pada Pemerintah Kabupaten Batang, Jawa Tengah) - Rachmi Kurnia Siregar; Wenny Maya Arlena (Avant Garde, 2017)
Post-Reform Corruption, Collusion and Nepotism (KKN) practices involvingexecutives, judiciary and legislatures continue to increase, as the State Budget(APBN) and the Regional Budget (APBD) sped up. One of the causes is theweakness of transparency of budget management. The regency government ofBatang, Central Java in the era of Yoyok Riyo Sudibyo Regent (2012-2017) seeksto create local budget transparency by holding Budget Festival (FA) containingaccountability report of APBD and development program of previous year. Inaddition to implementing e-Government, auctioning offices and establishingPublic Service Quality Improvement Unit (UPKP2). This study uses qualitativemethods, case studies and triangulation of data with the aim of: 1) Analyzing thecommunication policy process and communication policy making process FA 2)Assessing obstacles in the implementation of FA policy. Result of research:following the change of leadership, Regent of Batang period 2017-2022, Wihajiremove in the administration of the governance. However, Wihaji remainscommitted to implement transparent, accountable and participatory governanceby strengthening e-Government and Smart City. Pemkab Batang is advised tocontinue the transparency program of APBD governance through the BudgetFestival in accordance with the current condition. This gait is important tomaintain a strong social interaction between bureaucrats and people in the digitalage. As well as the identity and characteristics of the region in supporting thedevelopment of identity-based flagship areas to improve the competitiveness (citybranding).